Ultrasound of nerves of the lumbal plexus - S. A. Likhachev; N. I. Charnenka (Анналы клинической и экспериментальной неврологии, 2017)
Ultrasound examination of femoral, saphenous and lateral cutaneousfemoral nerves was performed in 25 healthy volunteers(50 extremities) with normal body weight, at mean age374.3 years. Examination procedure and topography of theinvestigated nerves are described. The nerves identification ispossible due to anatomical landmarks. Femoral and lateralfemoral cutaneous nerves were visualized in all cases. Cutaneousnerves are available for proper visualization in subjects with normallydeveloped subcutaneous fat. Structural features of nervesdidnt show statistically significant sexual and bilateral distinctions.Sonography is an accessible method for examination ofcertain lumbar plexus nerves.